PENOLAKAN STTP PENYAMPAIAN PENDAPAT DI MUKA UMUM OLEH PIHAK KEPOLISIAN DALAM PERSFEKTIF KEADILAN SOSIAL - Jamaluddin; Ardiansah; Andrizal (LPPM STIH Awang Long, 2025)
The freedom to express opinions in public is a constitutional right guaranteed by the 1945 Constitution of the Republic of Indonesia and further regulated by statutory laws. In practice, the exercise of this right often encounters obstacles, one of which is the refusal by the police to issue a Notice Receipt Letter (STTP). Such refusal may create legal and social problems, particularly when it is conducted without clear and proportional legal grounds, thereby potentially undermining the principle of social justice. This study aims to analyze the refusal of STTP for public demonstrations by the police from the perspective of social justice. The research employs a normative legal method using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary sources, which are analyzed through qualitative descriptive analysis. The findings indicate that any refusal to issue an STTP must be based on objective, proportional, and accountable legal considerations, while respecting human rights and the principle of social justice. Arbitrary, discriminatory, or non-transparent refusals may restrict citizens’ access to their constitutional rights. Therefore, a balanced approach is required between maintaining public order and safeguarding citizens’ rights to ensure that the exercise of public expression can be carried out in a democratic and socially just manner.